A Pooled Analysis of Clinical Pharmacology Trials Investigating the Pharmacokinetic and Pharmacodynamic Characteristics of Fast-Acting Insulin Aspart in Adults with Type 1 Diabetes - Heise, Tim; Pieber, Thomas R.; Danne, Thomas; Erichsen, Lars; Haahr, Hanne (Clinical pharmacokinetics, 2017)
Background Fast-acting insulin aspart (faster aspart) is insulin aspart (IAsp) in a new formulation aiming to mimic the fast endogenous prandial insulin release more closely than currently available insulin products. In a post hoc analysis of pooled data from six clinical pharmacology trials, the pharmacological characteristics of faster aspart and IAsp were compared. Methods The analysis included 218 adult subjects with type 1 diabetes from six randomised, double-blind, crossover trials in the faster aspart clinical development programme. Subjects received subcutaneous dosing (0.2 U/kg) of faster aspart and IAsp. In three trials, a 12-h euglycaemic clamp was performed (target 5.5 mmol/L; 100 mg/dL) to assess pharmacodynamics. Results The pharmacokinetic and pharmacodynamic profiles were left-shifted for faster aspart versus IAsp. Onset of appearance occurred 4.9 min earlier (95% confidence interval [CI] faster aspart-IAsp: [−5.3 to −4.4], p < 0.001), early exposure (AUC IAsp,0–30min ) was two times greater (estimated ratio faster aspart/IAsp 2.01 [1.87–2.17], p < 0.001) and offset of exposure ( t Late 50% Cmax ) occurred 12.2 min earlier [−17.9 to −6.5] ( p < 0.001) for faster aspart versus IAsp. Accordingly, onset of action occurred 4.9 min earlier [−6.9 to −3.0] ( p < 0.001), early glucose-lowering effect (AUC GIR,0–30min ) was 74% greater (1.74 [1.47–2.10], p < 0.001) and offset of glucose-lowering effect ( t Late 50% GIRmax ) occurred 14.3 min earlier [−22.1 to −6.5] ( p < 0.001) for faster aspart versus IAsp. Total exposure and total glucose-lowering effect did not differ significantly between treatments. Conclusions Faster aspart has the potential to better mimic the physiologic prandial insulin secretion and thereby to improve postprandial glucose control compared with IAsp. ClinicalTrials.gov identifiers: NCT02035371, NCT01924637, NCT02131246, NCT02033239, NCT02003677, NCT01618188.